Management of Supplemental Therapy with Tomato Juice (Lycopersicon Esculentum) to Reduce Cholesterol Levels in Adults in the Franciscan Community - Sinurat, Samfriati; Sigalingging, Vina Yolanda Sari; Hutasoit, Gresia Lamtiur (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
High blood cholesterol levels (hypercholesterolemia) can cause harm to the body, including increasing the risk of coronary heart disease, stroke, hypertension, and obesity. Preventing high cholesterol involves pharmacological and non-pharmacological therapies, including consuming tomato juice due to its high lycopene content. Lycopene is known for its antioxidant properties that may affect high cholesterol levels. This study was conducted to analyze the effects of supplement therapy with tomato juice on cholesterol levels in adults in the Franciscan Community of Santa Elisabeth in Medan 2023. The study used a quantitative research design with a pre-experimental method and a post-test group design approach. Purposive sampling was used to select 12 respondents who were given tomato juice for 14 days. The data was analyzed using the Wilcoxon test, and the results showed a p-value of 0.534 (p<0.05), indicating that tomato juice supplementation therapy had no significant effect on reducing cholesterol levels in adults in the Franciscan Community of Santa Elisabeth population in Medan. However, four respondents reported reduced cholesterol levels due to the complementary therapy with tomato juice, while eight did not experience the same effects. In conclusion, the utilization of tomato juice as a complementary therapy did not show a significant impact on reducing adult cholesterol levels. This prompts exploring other potential strategies for addressing this health concern.